2022
DOI: 10.3389/fimmu.2022.1023451
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the European League against rheumatism/American College of Rheumatology-2019 versus the Systemic Lupus International Collaborating Clinics-2012 versus the ACR-1997 classification criteria in adult systemic lupus erythematosus: A systematic review and meta-analysis

Abstract: AimTo evaluate the diagnostic performance of the American College of Rheumatology (ACR)-1997, the Systemic Lupus International Collaborating Clinics (SLICC)-2012, and the European League against Rheumatism (EULAR)/ACR-2019 classification criteria in adult patients with systemic lupus erythematosus (SLE).MethodsPubMed, Embase, Web of Science and Cochrane Library databases were searched for literature comparing the three classification criteria of ACR-1997, SLICC-2012 and EULAR/ACR-2019, which took clinical diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(104 reference statements)
1
6
0
Order By: Relevance
“…Nonetheless, as noted in the materials and methods, all patients were checked for strict compliance with SLICC/2012 classification criteria, as is applied at rheumatology center for SLE diagnosis. Although EULAR/ACR 2019 were not used, their sensibility has been shown to be similar as SLICC/2012 criteria [ 56 , 57 ] but there are differences on specificity, therefore could cause bias in the study. Also, the use of secondary sources of data collection leads to potential biases related to patient registries.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, as noted in the materials and methods, all patients were checked for strict compliance with SLICC/2012 classification criteria, as is applied at rheumatology center for SLE diagnosis. Although EULAR/ACR 2019 were not used, their sensibility has been shown to be similar as SLICC/2012 criteria [ 56 , 57 ] but there are differences on specificity, therefore could cause bias in the study. Also, the use of secondary sources of data collection leads to potential biases related to patient registries.…”
Section: Discussionmentioning
confidence: 99%
“…18 In contrast, the Chinese systematic review and meta-analysis released by Lu et al revealed almost equal diagnostic accuracy for EULAR/ACR and SLICC in the early stages of aSLE, with higher sensitivity (95% and 96%, respectively) for both of them in comparison to ACR 1997. 19 Moreover, previous adult studies have proposed applying a combination of classification criteria to enhance the sensitivity and allow earlier classification and treatment of more patients with high disease burden, 20 as comparable results with respect to the diagnostic sensitivity, specificity, and accuracy of SLICC and EULAR/ACR classification criteria were found. 21 Regarding the reliability of EULAR/ACR criteria among monogenic lupus, in our study, only 8 patients (6.2% of the cases) had confirmed genetic diagnosis of monogenic lupus, including 3 cases of C1q deficiency, 4 cases of DNASE1L3 deficiency, and 1 case of spondyloenchondrodysplasia (due to homozygous deletion in ACP5), and all of them met both the SLICC and EULAR/ ACR criteria.…”
Section: Discussionmentioning
confidence: 97%
“…18 In contrast, the Chinese systematic review and meta-analysis released by Lu et al revealed almost equal diagnostic accuracy for EULAR/ACR and SLICC in the early stages of aSLE, with higher sensitivity (95% and 96%, respectively) for both of them in comparison to ACR 1997. 19…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the most recent European League Against Rheumatism (EULAR) / ACR 2019 Classification Criteria differs by the obligatory presence of an ANA at titer of at least 1:80, as well as the presence of a minimum number of weighted laboratory and clinical criteria for the classification of SLE ( 7 ). This criteria has demonstrated a higher and similar sensitivity than the 1997 ACR Criteria and 2012 SLICC Criteria, respectively, and comparable specificity ( 8 ).…”
Section: Shortcomings Of the Current Diagnostic Algorithmmentioning
confidence: 96%